2022
DOI: 10.1111/gove.12743
|View full text |Cite
|
Sign up to set email alerts
|

Beyond consultocracy and servants of power: Explaining the role of consultants in policy formulation

Abstract: Prior research on consultants in policymaking described their expanding policy involvement and impact. This research focuses on consultants' policy formulation roles and on how and why these roles vary across jurisdictions and contexts. It draws on comparative research on healthcare policy in Ontario, Canada, and Victoria, Australia. Based on analysis of contracts and expenditure data, and 59 semi‐structured interviews, this research finds that consultants in Victoria are partners in formulation, used routinel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Consultants of different types have become an integral part of today's municipal governance. They are involved in a growing set of issues including climate change (Keele, 2019), privatization of social services and infrastructure (Hurl, 2017), health (Marciano, 2022a; Vogelpohl et al ., 2022) and cultural policy (Prince, 2012). Their influence is often depicted as ‘post‐political urban governance’—a wide set of planning and political processes, ranging from privatization to participatory planning, which are seen as flattening political debates and thus narrowing democracy (Metzger, 2018).…”
Section: Consultants Gurus and Post‐political Urban Governancementioning
confidence: 99%
See 1 more Smart Citation
“…Consultants of different types have become an integral part of today's municipal governance. They are involved in a growing set of issues including climate change (Keele, 2019), privatization of social services and infrastructure (Hurl, 2017), health (Marciano, 2022a; Vogelpohl et al ., 2022) and cultural policy (Prince, 2012). Their influence is often depicted as ‘post‐political urban governance’—a wide set of planning and political processes, ranging from privatization to participatory planning, which are seen as flattening political debates and thus narrowing democracy (Metzger, 2018).…”
Section: Consultants Gurus and Post‐political Urban Governancementioning
confidence: 99%
“…During the last four decades, consultants and experts have crept into various realms of municipal governance, advising cities about issues as diverse as economic and fiscal policy, technology, arts, culture, health and climate change (Prince, 2012;Hurl, 2017;Keele, 2019;Marciano, 2022a;Vogelpohl et al, 2022) and instructing them on whom to hire as service providers or even as consultants (Hurl and Vogelpohl, 2021). Their entry into the municipal governance scene is often identified in urban studies with a wider set of processes that are held to represent democratic deficiencies and labelled as 'post-political urban governance' (Metzger, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have repeatedly found a pronounced role for consultancies and think tanks as both key sources of policy ideas and advice, and as technical experts that government must go to given policy capacity shortages after years of budget cuts and austerity measures (Keele 2019;Marsh and Stone, 2004;Saint-Martin 2004;van den Berg et al 2019;Weiss 2018). In Australia, for example, van den Berg et al ( 2019) identify a continuous rise in the scope use of consultants for policy-related issues by the federal government, as well as a change in their substantial role, concurrent with stagnant levels of in-house staffing (see also : Marciano 2022), similar to the rise of the role and influence of consultants in Britain as well (Weiss 2018).…”
Section: Externalisationmentioning
confidence: 99%
“…In Australia, for example, van den Berg et al. (2019) identify a continuous rise in the scope use of consultants for policy-related issues by the federal government, as well as a change in their substantial role, concurrent with stagnant levels of in-house staffing (see also: Marciano 2022), similar to the rise of the role and influence of consultants in Britain as well (Weiss 2018).…”
Section: Learning From Westminster Style Governments: Pas Management ...mentioning
confidence: 99%
“…In policy sciences, there is an effort to learn about the mechanisms by which consultants influence the choice of policy courses, how they interact with processes and actors in policymaking, and what types of policy ideas and instruments they import. And public administration research is interested in how consultants are included in the standing administrative apparatus and particularly, how their use relates to changes in in‐house policy capacity and the status of the public service as a source of policy advice (Althaus et al, 2021; Marciano, 2022; van den Berg et al, 2019; Vogelpohl et al, 2022; Ylönen & Kuusela, 2019).…”
Section: Introductionmentioning
confidence: 99%